Mitochondrial DNA genetic variants are associated with systemic lupus erythematosus susceptibility, glucocorticoids efficacy and prognosis. (29th October 2021) - Teng, Ying; Yan, Zi-Ye; Wang, Lin-Lin; Wang, Yu-Hua; Zhang, Ting-Yu; Li, Zhen; Liu, Shuang; Cai, Jing; Chen, Yang-Fan; Li, Mu; Liu, Sheng-Xiu; Xu, Zhou-Zhou; et al.
Abstract: Objective: To investigate the associations of mitochondrial DNA (mtDNA) genetic variants with SLE susceptibility, glucocorticoid (GC) efficacy and prognosis. Methods: Our study was done in two stages. First, we performed whole mitochondrial genome sequencing in 100 patients and 100 controls to initially screen potential mtDNA variants associated with disease and GC efficacy. Then, we validated the results in an independent set of samples. In total, 605 SLE patients and 604 normal controls were included in our two-stage study. A two-stage efficacy study was conducted in 512 patients treated with GCs for 12 weeks. We also explored the association between mtDNA variants and SLE prognosis. Results: In the combined sample, four mtDNA variants (A4833G, T5108C, G14569A, CA514-515-) were associated with SLE susceptibility (all P BH < 0.05). We confirmed that T16362C was related to efficacy of GCs ( P BH = 0.014). Significant associations were detected between T16362C and T16519C and the efficacy of GCs in females with SLE ( P BH < 0.05). In the prognosis study, variants A4833G ( P BH = 0.003) and G14569A ( P BH = 9.744 × 10 −4 ) substantially increased SLE relapse risk. Female patients harbouring variants T5108C and T16362C were more prone to relapse ( P BH < 0.05). Haplotype analysis showed that haplogroup G was linked with SLE susceptibility ( P BH = 0.001) and prognosis ( P BH = 0.013). Moreover, mtDNA variant–environment interactions were observed. Conclusion: We identified novel mtDNA genetic variants that were associated with SLE susceptibility, GC efficacy, and prognosis. Interactions between mtDNA variants and environmental factors were related to SLE risk and GC efficacy. Our findings provide important information for future understanding of the occurrence and development of SLE.